2015
DOI: 10.1175/jcli-d-14-00210.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of the Location of Blocking Highs for Stratospheric Variability in a Changing Climate

Abstract: Previous research shows that blocking highs (BHs) influence wintertime polar stratospheric variability through the modulation of the climatological planetary waves (PWs) depending on the BH location. BHs over the Euro-Atlantic sector tend to enhance the upward PW propagation, and those over the northwestern Pacific Ocean tend to reduce it. Future changes are examined in the response of the wave activity flux to the BH location and their relationship with wintertime stratospheric variability in transient simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
(90 reference statements)
2
9
0
Order By: Relevance
“…Our results highlight the wide spectrum of behavior exhibited by the Arctic polar vortex in both time and altitude, which includes small localized weak/strong events, as well as prolonged and vertically deep ones. Distinguishing between such “major” and “minor” events has recently been highlighted by many as important for more completely describing the full variability of the stratosphere and its importance for numerous research topics including definitions of sudden warming events (e.g., Butler et al, ; Maury et al, ), polar chemical processing and ozone loss (e.g., Manney & Lawrence, ; Strahan et al, ), coupling with the troposphere (e.g., Dunn‐Sigouin & Shaw, ; Runde et al, ), understanding climate connections to, for example, the quasi‐biennial oscillation and El Niño/La Niña (e.g., Díaz‐Durán et al, ; Garfinkel et al, ; Iza et al, ), forecasting and prediction (e.g., Butler et al, ; Tripathi, Charlton‐Perez, et al, ), and defining and attributing events in climate models (e.g., Ayarzagüena et al, ; Kim et al, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our results highlight the wide spectrum of behavior exhibited by the Arctic polar vortex in both time and altitude, which includes small localized weak/strong events, as well as prolonged and vertically deep ones. Distinguishing between such “major” and “minor” events has recently been highlighted by many as important for more completely describing the full variability of the stratosphere and its importance for numerous research topics including definitions of sudden warming events (e.g., Butler et al, ; Maury et al, ), polar chemical processing and ozone loss (e.g., Manney & Lawrence, ; Strahan et al, ), coupling with the troposphere (e.g., Dunn‐Sigouin & Shaw, ; Runde et al, ), understanding climate connections to, for example, the quasi‐biennial oscillation and El Niño/La Niña (e.g., Díaz‐Durán et al, ; Garfinkel et al, ; Iza et al, ), forecasting and prediction (e.g., Butler et al, ; Tripathi, Charlton‐Perez, et al, ), and defining and attributing events in climate models (e.g., Ayarzagüena et al, ; Kim et al, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Many previous studies have noted that the anomalous upward fluxes of planetary waves from the troposphere to the stratosphere are closely related to tropospheric blockings (Quiroz, ; Mukougawa and Hirooka, ; Kuroda, ; Martius et al ., ; Castanheira and Barriopedro, ; Nishii et al ., , ; Woollings et al ., ; Vial et al ., ; Ayarzaguena et al ., ). On the other hand, Marshall and Scaife () found that the predictability of stratospheric warmings and Atlantic blocking signatures can be improved when the stratosphere was better represented in a numerical model, implying a role of the stratosphere in the evolution of tropospheric blockings.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to influencing fields near the surface, blocking flow also impacts the winter polar stratosphere. In particular, the location, shape, and distribution of blocks are linked to planetary wave propagation and vortex displacements (Ayarzäguena et al, 2015;Martius et al, 2009;Nishii et al, 2011).…”
Section: Introductionmentioning
confidence: 99%